Digital resilience of sports communities in a Facebook group during military conflict - Sergii Iermakov; Georgiy Korobeynikov (Pedagogy of Health)
Background and Study Aim. In the context of military conflict, analyzing online interactions becomes a crucial tool for studying social and emotional processes. This study aims to analyze the sentiments, activity patterns, and key themes of interaction among participants in a sports Facebook group during wartime.